Microstructure and mechanical properties of additive manufactured Ti-6Al-4V components by annular laser metal deposition in a semi-open environment. (March 2021) - Cheng, Dongji; Zhang, Jinchao; Shi, Tuo; Li, Gang; Shi, Jianjun; Lu, Lin; Fu, Geyan
Highlights: The Ti-6Al-4V block fabricated by ALMD in a semi-open environment is reported. A developed coaxial double-layer gas nozzle can prevent atmospheric contamination. Martensitic microstructure was formed due to high cooling rate by annular laser beam. The strength of ALMD-produced sample is higher than that of wrought material. Abstract: Annular laser metal deposition (ALMD) is a novel additive manufacturing technology that fabricates near-net shaped components. In this research, the Ti-6Al-4V block was deposited by powder-feed ALMD process in a semi-open environment. A developed coaxial double-layer shielding gas nozzle was used to generate a local inert atmosphere around the molten pool to prevent atmospheric contamination, replacing a sealed chamber. The particular impurity levels, microstructure and mechanical properties were investigated. The results show that ALMD-produced Ti–6Al–4V in a semi-open environment can achieve a shiny silver surface finish, and the content of interstitial elements as oxygen, nitrogen, and hydrogen is well below those allowable for ASTM Grade 5. An acicular martensitic microstructure within the β columnar grains is formed due to high cooling rate. The room temperature tensile test demonstrates the as-deposited sample has a higher strength and lower elongation compared with the wrought material.